O012 Joint-specific synovial TGF-Β1-induced AXL expression determines the outcome of inflammatory arthritis between ankle and knee joints. (21st February 2018) - Waterborg, CEJ; Broeren, MGA; Blaney Davidson, EN; Koenders, MI; Lent, PLEM van; van den Berg, WB; van der Kraan, PM; van de Loo, FAJ
Abstract : Introduction: Rheumatoid arthritis (RA) manifests in a symmetrical fashion in anatomically distinct synovial joints. The innate immune system, which plays a crucial role in the pathogenesis of RA, is regulated by anti-inflammatory feedback mechanisms such as the tyrosine kinase receptor family TYRO3, AXL and MER. Of importance, AXL is mainly expressed on sentinel cells. Objectives: To investigate the synovial expression of AXL and its putative anti-inflammatory role in arthritis. Methods: KRN serum transfer arthritis was induced in Axl -/- and wild-type mice. Knee and ankle joints were scored macro- and microscopically. Synovial gene and protein expression of Axl was determined in naive and TGF-β1-overexpressing joints. AXL expression was determined in M1-like or M2-like macrophages and RA synovium. Human macrophages and synovial micromasses were stimulated with TGF-β1 or the AXL inhibitor R428. Results: The ankle joints of Axl -/- mice showed an increased macroscopic disease score during arthritis development (p<0.001 at day 7). In agreement with this, ankle joints of Axl -/- mice showed exacerbated arthritis pathology whereas no effect of Axl gene deletion was observed on gonarthritis pathology. To explain this spatial difference, we examined the synovium of naive mice. In contrast to the knee, the ankle synovial cells prominently expressed AXL. Moreover, the M2-like macrophage phenotype was the dominant cell type in the naive ankle joint. Human M2-like macrophages expressed higher levels of AXL and blocking AXL increased their inflammatory response. In the murine ankle synovium, gene expression of Tgfb1 was increased and Tgb1 correlated with Axl (Pearson r=0.8860, p=0.0012). Moreover, TGFB1 and AXL expression also correlated in human RA synovium (Pearson r=0.7233, p=0.0035). In human macrophages and synovial micromasses, TGF-β1 enhanced AXL expression. Moreover, TGF-β1 overexpression in naive murine knee joints induced synovial AXL expression. Conclusions: Differences in synovial AXL expression are in accordance with the observation that AXL dampens arthritis in ankle, but not in knee joints. We provide evidence that the local differences in AXL expression could be due to TGF-β1, and suggest similar pathways operate in RA synovium. Disclosure of interest: None declared